Estimating attractiveness, hierarchy and catchment area extents for a national set of retail centre agglomerations. (January 2016) - Dolega, Les; Pavlis, Michalis; Singleton, Alex
Abstract: There is a legacy of research aiming to conceptualise and empirically estimate retail store catchment areas, however, a dearth that frames such considerations within the context of retail agglomerations and their position within regional or national networks. As a result, this paper provides an extension to single store or shopping centre retail catchment estimation techniques, and presents an empirically specified and tested production constrained model for a national network of retail centres in the UK. Our model takes into account the spatial interactions between potential customers and a hierarchical network of retail centres to estimate patronage probabilities and catchment extents. The model is tested for a large metropolitan area vis-à-vis real world shopping flows recorded through a survey of shoppers. Finally, we present an open source software tool for custom model fitting, and discuss a range of theoretical and empirical challenges that such a model presents. Highlights: This study estimates catchments areas for a national network of retail centres in the UK. The model estimates retail catchment extents at a Lower Super Output Area level of granularity. This paper discusses a range of theoretical and empirical challenges that such a model presents. An open source software tool for custom model fitting is also presented.